Eat this, not that! : the best (& worst) foods in America - Zinczenko, David (Rodale, 2009)
Men's health editors share their advice on the best & worst foods, "healthy" foods, restaurants, breakfasts, salads, burgers, pizzas, sandwiches, sushi, supermarket foods, snack foods, frozen foods, drinks, beer & wine, foods for any symptom, foods for your blood pressure, foods for your cholesterol, foods for your blood sugar, foods you've never heard of, food additives, mall foods, drive-thru foods, foods for kids, and desserts in America.